Ethos discursivo e posicionamento deflagrados no interdiscurso das narrativas de vítimas de abuso sexual na rede social X - Couceiro, Marillia Arruda (2024)
This study aims to analyze the narratives of victims of sexual abuse published on the social network X, based on the study of the interdiscourse between these narratives, in order to reveal how the positioning and discursive ethos of these victims are constructed in their narratives about the sexual abuse they suffered as minors. Based on an interdisciplinary approach, this study sought to understand how the victims' narratives can contribute to social progress against the crime of sexual abuse against minors, taking into account interdiscursivity, discursive ethos and positioning. To this end, this work is based on the studies of Maingueneau (2008, 2010, 2015, 2022), Ribeiro (2023) and Maia-Vasconcelos (2022). As a result, we observed that the victims construct their ethos by alternating it with the point of view of their childhood self and their adult self, as well as drawing on the interdiscourses of other victims who take a discursive stance, based on their life narratives, against silencing. We also observed that it is from the interdiscourse that many victims, previously silenced, choose to tell their stories and position themselves in relation to what happened.